Application of the Naive Bayes Classifier Method and Fuzzy Analytical Hierarchy Process in Determining Books Eligible for Publishing - Irwansyah, Mochamad Denny; Negara, Teguh Puja; -, Erniyati; Citra, Puspa (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2024)
The manuscript selection process is the process of assessing manuscripts worthy of publication. The Editor's job is to provide an evaluation of each manuscript based on the assessment criteria and sub-criteria. By using a decision support system, it can make it easier for policymakers to determine the suitability of a manuscript. In this research, a decision support system is applied to select papers that are worthy of publication, namely the Fuzzy Analytical Hierarchy Process (F-AHP) method for selecting the suitability of manuscripts using subjective criteria and the Naïve Bayes method for classifying books based on their genre. The test results using the F-AHP method produced an accuracy rate of 83.33% using 30 books out of 150 books and using the Naïve Bayes method produced an accuracy rate of 80% using 30 books from the internet. This system uses the Visual Studi Code IDE, Firebase, and Pythonanywhere as its database with an Android display.